New records and two new species of Xiphocentron Brauer 1870 (Trichoptera, Xiphocentronidae) from southern Atlantic Forest, Brazil - Vilarino, Albane [UNESP]; Bispo, Pitagoras C. [UNESP] (Magnolia Press, 2020)
Xiphocentron is the most species-rich genus of the pantropical family Xiphocentronidae. Among its five subgenera, Antillotrichia is the most diverse and the only one to occur in South America and Antilles. In the present study, two new species of Xiphocentron (Antillotrichia) are described from southern Atlantic Forest, Brazil. Xiphocentron gwarakeraba sp. nov. is diagnosed by the very elongate inferior appendage not bearing spines and with a simple mesal sclerite; X. muelleri sp. nov. is diagnosed by the inferior appendage with its ventral margin produced posterad and distinctly truncate. New distributional records are provided for X. acqualume, X. jaguare, X. kamakan, and X. maracanan. Additional nongenital diagnostic characters am presented for X. jaguare, and intraspecific morphological variations of forming fork II (R3 and R4) and male genitalia are described for X. maracanan.
Keywords: Aquatic insects; biodiversity; caddisflies; Neotropical; taxonomy